2023
DOI: 10.3390/nano13030567
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Emulsifying Ability of Deoxycholate through Dynamic Interaction with Layered Double Hydroxide

Abstract: The emulsifying ability of the naturally occurring surfactant deoxycholic acid (DCA) was improved by dynamic interaction with nanometric layered particles, layered double hydroxide (LDH). As DCA molecules are rigid due to the facial configuration of hydrophobic–hydrophilic groups, they tend to form molecular aggregation in an acidic condition or imbalanced water–lipid ratios. In this study, the homogeneous hybrids of DCA and LDH were obtained by the in situ growth of LDH at a DCA molecule. The DCA−LDH hybrid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…As the LDH moiety can be soluble in acidic media, the colloidal stability of DA-LDH in acidic condition may be different from that in neutral pH. However, it can be suggested that the dissolution of LDH in acidic media plays a buffering role in protecting DA moiety from the attack of acid [50,51].
Figure 9DLS size distribution by intensity of the DL-R prepared at pH 7 and pH 12 in water and pH adjusted by using 1 M of NaOH.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the LDH moiety can be soluble in acidic media, the colloidal stability of DA-LDH in acidic condition may be different from that in neutral pH. However, it can be suggested that the dissolution of LDH in acidic media plays a buffering role in protecting DA moiety from the attack of acid [50,51].
Figure 9DLS size distribution by intensity of the DL-R prepared at pH 7 and pH 12 in water and pH adjusted by using 1 M of NaOH.
…”
Section: Resultsmentioning
confidence: 99%
“…in a variety of media. Indeed, the DA-LDH could be used in the formulation of oil in water emulsion [ 50 ], which can be further used as cosmetics for transdermal delivery platforms.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study the inclusion of sodium cholate or SDC as edge activators incorporated into liposomes resulted in increased transdermal absorption vis-à-vis Tween 80. Hence, SDC was observed to improve the fluidity of vesicles to spontaneously squeeze though channels in the SC and prevents vesicle rupture when crossing through the different skin layers, eventually increase the deformability of the system 27 29 .…”
Section: Introductionmentioning
confidence: 99%